EXAMPLES FROM THE QURAN AND HUMAN NATURE: PRACTICAL APPLICATION IN THE MODERN ERA - Arslan Arif; Muhammad Huzaifa; Qudeer Ahmad (Journal of Religion and Society, 2025)
The parables of the Quran, known as Amthal ul-Quran, are integral elements of divine wisdom, crafted to guide humanity toward spiritual enlightenment and moral rectitude. These parables employ vivid and relatable analogies to elucidate complex spiritual, ethical, and social truths, making them accessible to people of all intellectual capacities and cultural backgrounds. By bridging abstract ideas with tangible realities, they address universal human experiences and dilemmas, offering solutions rooted in timeless principles. This study delves into the profound relevance of Quranic parables in understanding human nature, reflecting on their alignment with contemporary societal challenges, such as rampant materialism, ethical deterioration, and spiritual crises. It examines how these narratives resonate with the human psyche, transcending historical and cultural barriers to provide enduring guidance. The analysis highlights their practical applications in promoting values such as justice, compassion, and self-awareness, which are essential for individual and collective well-being. Key recommendations include incorporating Quranic parables into educational curricula to enhance moral and ethical understanding among students, fostering their practical application through structured community training programs, and encouraging interdisciplinary research to explore their relevance in addressing modern-day challenges. Additionally, this research emphasizes the potential of Quranic parables to inspire personal growth, cultivate resilience, and guide societal transformation in an era marked by rapid change and moral ambiguity. Ultimately, this study reaffirms the Quranic parables' timeless significance as tools for nurturing holistic development, strengthening spiritual connections, and promoting a harmonious balance between personal aspirations and societal responsibilities. Their enduring wisdom remains a beacon of light, offering pathways to overcome challenges and achieve a just, equitable, and spiritually enriched world. Keywords: Examples of the Quran, Human Nature, Practical Application, Contemporary Relevance